KAJIAN ILMU AL-QUR’AN: NASAKH WA MANSUKH - Fajaria, Ernadatul; Fatoni, Muhammad (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2023)
The Al-Qur'an has two sides, namely that the Al-Qur'an is a book of Muslims which has no differences in it (ikhtilaf) but on the other hand there is a verse in the Al-Qur'an which mentions nasakh, namely in Q.S. Al-Baqarah verse 106. Because of this, there are differences of opinion among the scholars into two groups. First, those who accept and support naskh, which means there is an annulment in the Koran. Second, they do not accept nasakh in the sense of negating the law directly revealed by Allah SWT, and they interpret nasakh as the same as takhsis, or more precisely as specialization. Therefore, it is not surprising that the discussion of Nasikh Wa Mansukh is an interesting discussion to study.